Implementasi Wazuh SIEM untuk Manajemen Log Event di Pesantren Teknologi Informasi dan Komunikasi Jombang - Saputra, Faruq Aziz; Dharmawan, Tubagus Rizky; Rustianto, April (Jurnal Informatika Terpadu, 2024)
Information Security is essential for organizations and companies in the current digital transformation era. As a technology-oriented education, Pesantren Teknologi Informasi dan Komunikasi (PeTIK) Jombang requires a reliable security system, considering the increasing security risks. This research proposes the implementation of Wazuh as a Security Information And Event Management (SIEM) integrated with Telegram Bot for real-time system security detection and analysis. Wazuh was chosen because it has advantages in log management, ease of use, and strong community support. This research describes the implementation process of Wazuh, incident log visualization, and integration with Telegram Bot as an alert system. It tests attacks such as Bruteforce, DoS Attack (SYN Flood), and SQL Injection, showing that Wazuh effectively detects and responds to potential threats. Log visualization provides benefits in terms of efficiency and effectiveness in handling security incidents. In addition, Wazuh's integration with Telegram can provide notifications via Telegram Bot in real-time. This research also involves performance testing by monitoring the CPU and memory of the Wazuh server, and results show that the CPU and memory are still within normal limits when an attack occurs.